Relationship of Physical Factors to the Occurrence of Injuries in Young Gymnasts - Yuria Kobayashi; Yasuharu Nagano; Makoto Suzukawa (North American Sports Medicine Institute, 2024)
# Background There is a large population of young athletes who participate in gymnastics, and the prevention of injury in junior athletes is considered important. However, few studies have prospectively investigated the relationship between physical factors and the occurrence of injury. # Purpose To investigate the physical characteristics that are factors in the injury occurrence in elementary and junior high school gymnasts. # Study Design Prospective observational study. # Methods A total of 36 healthy young gymnasts (at national competition level) were enrolled in the study. Once a week for 23 weeks, injuries were prospectively investigated using self-report questionnaires under the supervision of a research staff. Joint range of motion (hip, ankle, shoulder, and wrist), tightness (Thomas test, Ely test, straight leg raise \[SLR], triceps surae, combined abduction test \[CAT], horizontal flexion test \[HFT]), and muscle elasticity (multifidus) were assessed to compare differences in physical function between injured and non-injured participants. # Results Injuries occurred most commonly in the wrist (42.1%), lower back (30.2%), and foot (9.5%) among males, whereas heel (22.2%), knee (16.0%), and lower back (12.8%) were the most common injury sites among females. Wrist injuries in male athletes showed decreased shoulder joint range of motion, and lower back injuries showed decreased hip and shoulder joint range of motion. Lower back injuries in female athletes showed decreased hip extension mobility. Heel and knee joint injuries in females also showed increased range of motion and decreased tightness. # Conclusions The results of this study indicate that the factors related to flexibility differ according to injury location. Further studies are required to clarify the physical factors that influence injury occurrence by examining the effects of the gymnasts' muscle strength, age, individual factors, and left-right differences. # Level of Evidence 3